PENERAPAN PIDANA MATI BAGI PENGEDAR NARKOBA PERSFEKTIF HAK AZAZI MANUSIA - Putri Sari Nilam Cayo; Enni Merita (Justici, 2021)
The death penalty is still ongoing and has not been abolished in Indonesia, people have different opinions in responding to it as many countries have abolished the death penalty. On the one hand, there are community groups expressing their support that the death penalty is still needed in Indonesia, moreover, it is still legally recognized. Meanwhile, on the other hand, there are groups of people who want the death penalty to be abolished. The application of the death penalty has actually been answered in the decision of the Constitutional Court on the petition for judicial review of Law Number 22 of 1997 concerning Narcotics against the 1945 Constitution. 1997 on Narcotics is not against the Constitution. Thus, it can be concluded that in analogy, capital punishment is not an unconstituional act.